RAMEN DAN PRESENTASI IDENTITAS BUDAYA JEPANG - Muhamad Regi Rashif Razaqa; Pitri Haryanti (Fakultas Ilmu Budaya, Universitas Komputer Indonesia, 2023)
The purpose of this study was to find out the history of the entry of ramen into Japan, and what kind of changes made ramen uniquely Japanese even though the actual ramen originated in China. To support this research, the authors used a descriptive method with a qualitative approach. Results show that ramen first entered Japan in 1880 when Japan began to open ports. Migrants from China opened a restaurant whose main menu was noodle soup. This is because in 1910 Japanese restaurants hired cooks from China to turn their food into delicious foods containing ingredients not previously used in the Chinese version of noodle soup. With the existence of Japanese culinary culture such as me de taberu. Japanese ramen or nihonfuu is very different from noodle soup originating from China. Keywords: Ramen, culinary, culture, Japan